Analisis Sentimen Terhadap Layanan Aplikasi Jenius di Media Sosial Menggunakan Alogritma Long Short-Term Memory - Husna, Modesta Binti; Gata, Windu (STMIK Banjarbaru, 2024)
The Jenius application was launched in 2015 by PT Bank BTPN Tbk, introducing innovation in digital banking services with an active presence on social media platforms like YouTube, Twitter (X), and Instagram. Users often provide reviews that can influence the perception and reputation of the application. This study aims to assist Bank BTPN in enhancing its services by analyzing positive, neutral, and negative user reviews. The method used is the Long Short-Term Memory (LSTM) model for sentiment analysis. The data analyzed consists of 856 comments on YouTube with the keyword